The correlation of personality characteristics and social factors with identity styles in adolescents of Golestan, Iran - Ghorbani, Alireza; Abdullah, Haslinda; Ahmad Ali, Nobaya; Redzuan, Ma'rof (Wiley-Blackwell Publishing, 2015)
The present study aims to examine the relationship between personality characteristics, social factors, and identity styles in adolescents. A correlational method was employed. Statistical population in this research consists of all high-school and pre-university students living in Golestan province during the year this research was being conducted.The sample included students (n=380) aged 17 and 18.In this study, the stratified random sampling method was used.Data were collected through self-administered questionnaires (identity styles, including: informational identity style, normative identity style, diffuse/avoidance style, commitment and social factors, including: family relationship, school and peer group relationship and personality characteristics, including: agreeableness, neuroticism, extraversion, conscientiousness and openness to experience.Descriptive and inferential statistics such as Mean, Standard Division, and Pearson correlation were used. The findings showed that there were significant correlations between personality characteristics and identity styles in adolescents. Significant correlations between social factors and identity styles in adolescents were also observed. In addition according to the results, a moderate and positive correlation was observed between informational and normative styles, informational style and commitment, normative style and commitment, as well as commitment and neuroticism. Additionaly, the results of the study supported theories like social cognitive theory, General other theory, and triat approach. The results shed new light on the processes involved in the personality characteristics and social factors of adolescents’ styles of identity exploration.